The floor of heaven : a true tale of the last frontier and the Yukon gold rush - Blum, Howard (Crown Publishers, 2011)
Using primary source materials from three individuals around whom the narrative revolves, best-selling author Blum tells a fascinating story of the 1897 Klondike Gold Rush.